Design of Boost Converter Integrated with Graphical User Interface - Sesrima Badri; Krismadinata Krismadinata (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2020)
This article discusses the design of a Boost type of DC-DC converter with a monitoring GUI. The increase in the output voltage of the converter is done by adjusting the pulse width (PWM). Change the size of the PWM is done by using a switching component in the form of MOSFETs, as well as the use of a gate drive that serves as a signal and security reinforcement between the control circuit and its main circuit. The input voltage of the converter is designed at 12VDC, with an output voltage of 12VDC-24VDC. In this study the GUI was successfully added to display several variables such as voltage (Volt), current (Ampere), as well as graphs of the input and output voltage of the boost converter. GUI monitoring of the converter can be viewed via a PC using Visual Studio 2012 software. Artikel ini membahas tentang perancangan sebuah rangkaian konverter DC-DC tipe Boost (penaik tegangan) dengan GUI monitoring. Kenaikan tegangan keluaran dari konverter dilakukan dengan mengatur lebar pulsa (PWM). Pengubahan besar kecilnya PWM dilakukan dengan meggunakan komponen switching berupa MOSFET, serta penggunaan gate drive yang berfungsi sebagai penguatan sinyal dan pengaman antara rangkaian kontrol dan rangkaian utamanya. Tegangan masukan dari konverter dirancang sebesar 12VDC, dengan tegangan keluaran 12VDC-24VDC. Dalam penelitian ini GUI berhasil ditambahkan untuk menampilkan beberapa variabel seperti tegangan (Volt), arus (Ampere), serta grafik tegangan masukan dan keluaran dari konverter boost. GUI monitoring dari konverter dapat dilihat melalui PC menggunakan software Visual Studio 2012.